1 < 2 and 2 < 3: Non-Linguistic Appreciations of Numerical Order - Anderson, Ursula; Cordes, Sara (Frontiers in Psychology, 2013)
Ordinal understanding is involved in understanding social hierarchies, series of actions, and everyday events. Moreover, an appreciation of numerical order is critical to understanding to number at a highly abstract, conceptual level. In this paper, we review the findings concerning the development and expression of ordinal numerical knowledge in preverbal human infants in light of literature about the same cognitive abilities in nonhuman animals. We attempt to reconcile seemingly contradictory evidence, provide new directions for prospective research, and evaluate the shared basis of ordinal knowledge among nonverbal organisms. Our review of the research leads us to conclude that both infants and nonhuman animals are adapted to respond to monotonic progressions in numerical order, consonant with mathematical definitions of numerical order. Further, we suggest that patterns in the way that infants and nonhuman animals process numerical order can be accounted for by changes across development, the conditions under which representations are generated, or both.